DOMINANT BODY SOMATOTYPE AND GENDER DIFFERENCES IN HAND GRIP STRENGTH OF YOUNG ADULTS IN A NIGERIAN UNIVERSITY (Journal of Biomedical Investigation, 2024)
Background: Hand Grip Strength (HGS) is a measure of the grasping power of an individual and a known indicator of physical capability in males and female who evidently have different body compositions, and may be used to evaluate patient recovery progress throughout injury treatment and rehabilitation.Aim/ Objective: To determine the influence of dominant body somatotype and gender on hand grip strength of young Adults in a Nigerian University. Material/Methods: This was an ex-post facto research which was carried out among 162 undergraduates in Southern Nigeria. An electronic handheld dynamometer was used to evaluate the handgrip strength while the Heath-Carter Instruction Manual was used to determine the anthropometric dominant body somatotype. Data collected was summarized using descriptive statistics of frequency, percentages, mean and standard deviation, and analyzed using inferential statistics of Pearson’s Product Moment Correlation, Two-way and one-way ANOVA at an alpha level of 0.05.Result: Endomorphy was more predominant in the population than mesomorphy and ectomorphy (48.1%, 25.3% and 26.5%). A significant effect was found in dominant body somatotype on the left and right hand grip strength (t = 11.959, p = 0.001 and t = 9.817, p = 0.001) with mesomorphy having the strongest effect on HGS, Furthermore, differences between genders and dominant body somatotypes in the left and right HGS was not significant statistically (F2 = 0.821, p = 0.442) and (F2 = 0.553, p = 0.576) but there was a significant main effect for dominant somatotype (F1 = 149.188, p = 0.001) and (F1 = 135.552, p = 0.001). Mesomorphic males were seen to have greater HGS. Result also revealed significant correlations between height and weight and HGS of both left and right hands (r = 0.453, p = 0.001), (r = 0.408, p = 0.001 and r = 0.420, p = 0.001).Conclusion: Dominant body somatotypes as well as gender differences had a very significant influence on handgrip strength.
Keywords: Somatotype; Anthropometry; Kinesiology; Body Mass Index; Biomechanics